Trends, outcomes and knowledge gaps in mobile apps for reproductive endocrinology and infertility: a scoping review protocol - Alba Regina de Abreu Lima; Emerson Roberto dos Santos; Aline Russomano de Gouvêa; Natália Almeida de Arnaldo Silva Rodriguez Castro; João Daniel de Souza Menezes; Matheus Querino da Silva; Helena Landin Gonçalves Cristóvão; Cíntia Canato Martins; Jéssica Gisleine de Oliveira; Patrícia da Silva Fucuta; Alexandre Lins Werneck; Gerardo Maria de Araújo Filho; et al. (BMJ Open)
Introduction Infertility is a complex condition that affects millions worldwide, with significant physical, emotional and social implications. Mobile apps have emerged as potential tools to assist in the management of infertility by offering features such as menstrual cycle tracking, ovulation prediction, fertility education, lifestyle modification guidance and emotional support, thereby promoting reproductive health. Despite promising advancements such as the development of apps with sophisticated algorithms for ovulation prediction and comprehensive platforms offering integrated fertility education and emotional support, there remain gaps in the literature regarding the comprehensive evaluation of mobile apps for reproductive endocrinology and infertility. This scoping review distinguishes itself by systematically mapping and synthesising evidence on mobile apps specifically for reproductive endocrinology and infertility, unlike previous reviews that may not have focused exclusively on this intersection. This review aims to analyse recent trends, identify outcomes used to assess usability and highlight knowledge gaps.Methods and analysis This scoping review will adhere to the methodological frameworks outlined by Arksey and O'Malley and Levac et al, alongside the Joanna Briggs Institute’s recommendations. The research question, ‘What is known about mobile apps in reproductive health and infertility?’ was formulated using the Population, Concept, Context (PCC) strategy. We will include studies published from January 2019 to April 2024 in English, Portuguese and Spanish that focus on the use of mobile apps in reproductive health and infertility. Searches will be conducted across electronic databases (EMBASE, ERIC, PubMed, Science Direct, Scopus and Web of Science) and grey literature sources. Two independent reviewers will carry out the study selection using Covidence software. Data extraction will follow a standardised format and will be synthesised narratively using tables and graphs. Expert consultations will be conducted to validate the findings.Ethics and dissemination Ethical approval is not required for this scoping review as it will only use published data. The findings will be disseminated through publication in a peer-reviewed journal, conference presentations and stakeholder meetings. The review protocol will be registered with the Open Science Framework to ensure transparency and reproducibility.